Description of five new coral associated Barnacles of the genus Trevathana (Balanomorpha: Pyrgomatidae) in Pacific Waters - Chan, Benny Kwok Kan; Chen, Yi-Yang; Achituv, Yair; Lin, Hsiu-Chin (Zootaxa, 2017)
Five new species of coral inhabiting barnacles of the genus Trevathana (Balanomorpha: Pyrgomatidae), T. dongshaensis sp. nov., T. conica sp. nov., T. doni sp. nov., T. longidonta sp. nov. and T. taiwanus sp. nov., are described. These species are found in West Pacific waters including Japan, Taiwan (mainland and adjacent outlying islands including Dongsha Atoll) and Papua New Guinea. The species exhibit morphological differences in the scutum, the tergum, and cirri II and III, and form distinct clades in a phylogenetic tree based on DNA sequences of two genes, 12S rDNA and cytochrome C oxidase subunit I. Three of the five species, T. dongshaensis sp. nov., T. conica sp. nov. and T. taiwanus sp. nov., have relatively narrow distribution ranges and were recorded from the Dongsha Atoll (T. dongshaensis sp. nov. and T. conica sp. nov.) and the Taiwanese mainland (T. taiwanus sp. nov.). Trevathana longidonta sp. nov. and T. doni sp. nov. have wider distributions. Trevathana longidonta sp. nov. was collected from Japan, Taiwan and Dongsha Atoll and T. doni sp. nov. was collected from Taiwan, Dongsha Atoll and Papua New Guinea. In the waters of Japan, Taiwan and Dongsha Atoll, all the recorded Trevathana species inhabit corals of the family Merulinidae. However, in Papua New Guinea, T. doni sp. nov. is also recorded in the coral Oxypora, belonging to the family Lobophylliidae, and individuals living on Lobophyllidae and Merulinidae did not exhibit great variation in the divergence of the COI and 12S genes.